Can Home Industry Support Employment Provision in Kota Pari Village? - Ahmad Fadlan; Sanusi Ghazali Pane; Ika Herawaty Rangkuty (International Publisher, 2024)
The aim of this study was to assess the contribution of home industries in Kota Pari Village to employment generation. Home industries play a vital role in expanding job opportunities, providing essential economic services to the community, reducing unemployment, and enhancing people's well-being. This study utilized library research methods, gathering information from reference centers and scientific journals to directly access and analyze data. A more efficient industrial sector at the national level necessitates the presence of small companies within the manufacturing industry. The growth of home industries in rural areas can boost the local economy through diverse business activities and community skill development. The research findings indicated that prioritizing the industrial sector in the economic structure leads to a positive impact on poverty reduction. Additionally, focusing on creating more job opportunities is crucial for poverty alleviation. Moreover, facilitating the transition from agriculture to the industrial sector is essential. Lastly, managing population growth is also imperative in conjunction with these efforts.